A cross-cultural study of the sports happiness perception among Korean, Chinese, and Japanese elite swimming athletes - Jin, H.; Chen, G.; Hee, S. Y. (International Journal of Applied Sports Sciences, 2017)
While previous research highlights the important value that sports happiness can have for athletes` quality of life, limited research has examined the sports happiness of elite athletes. The purpose of this study was to examine the difference between Korean, Chinese, and Japanese Elite Swimming athletes` sports happiness and, if there was any, how the result was similar and different cross-culturally/nationally. Semi-structured interviews were conducted with total 12 elite swimming athletes. Participants were both males (n = 6) and females (n = 6), who were between 19-23 years old with average 13.9 years of swimming experience. Interviews were transcribed verbatim and were analyzed with a content analysis procedure in which raw meaning units were grouped into salient themes. Athletes` responses regarding happiness derived from this in-depth interview revealed five categories: 1) athletes` perception of happiness. 2) happiness in everyday life 3) happiness in practice and competition situations 4) coach-athlete relationship 5) material happiness. The participants perceived their happiness were associated with a pleasure, satisfaction and in practice and competition situation and most of athletes answered that happiness is when they have good results. But material rewards and benefits given to them cannot be seen happiness but a supporting. Social and cultural processes making these different outcomes are discussed.